Evaluation of cardioprotective effect of silk cocoon (Abresham) on isoprenaline-induced myocardial infarction in rats - Ritesh Kumar Srivastav; Hefazat Hussain Siddiqui; Tarique Mahmood; Farogh Ahsan (Mashhad University of Medical Sciences, 2013)
Objective: The study was conducted to evaluate cardioprotective effect of silk cocoon (Abresham) Bombyx mori (B. mori) on isoprenaline-induced myocardial infarction. This study deals with the cocoons, which is called Abresham in the Unani system of medicine. It is one of the 64 drugs which Avicenna has mentioned in Avicenna's tract on cardiac drugs and used in the treatment of cardiovascular diseases. Abresham is a chief ingredient of the two very famous Unani formulation viz. Khamira Abresham Sada, and Khamira Abresham Hakim Arshad Wala. Materials and Methods: The ethanolic extract of B. mori (Abresham) silk cocoons in the dose of 250 mg/kg and 500 mg/kg body weight was administered orally for 28 days before isoprenaline administration to test their cardioprotective effect. Isoprenaline (85 mg/kg) was administered subcutaneously on days 29th and 30th, respectively in order to induce myocardial infarction. Results: The parameters for evaluation of cardioprotective activity were the physical parameters and the biochemical estimations. The physical parameters were gross examination of heart, heart weight/body weight ratio and histopathology examination. In biochemical estimations, the activity of various cardiac enzymes such as aspartate transaminase, alanine transaminase, creatinine kinase, lactate dehydrogenase, and the gold marker troponin-I were determined. The levels altered by isoproterenol were restored significantly by the administration of the both doses of test extract especially at higher dose. Conclusion: The result of this study shows that alcoholic extract B. mori hassignificant cardioprotective activity against isoprenaline-induced myocardial infarction.